ANTECEDENTS DARI BRAND EQUITY PADA HOTEL SANTIKA DI BSD TANGERANG - Asriani Susiati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2013)
This study refers to previous studies, by kevin kam Fung So and Ceridwyn King (2009). The background of this research was to prove the management approaches that brand equity as the key assets for hotel industries and provide brand manger hotel to evaluate brand equity as an outcome brand strategies. The objectives of this research was : (a) the positive effect of company’s presented brand to brand awareness, (b) the positive effect of company’s presented brand to brand meaning, (c) the positive effect of external brand communications to brand awarenessm, (d) the positive effect of external brand communications to brand meaning, (e) the positive effect of customer experience with company to brand meaning, (f) the positive effect of brand awareness to brand equity, (g) the positive effect of brand meaning to brandequity. The design of this research applies a survey toward unit of analysis on the hotel and to interview the customers for testing hypothesis. Meanwhile the required data consist of six variables; company presented brand, external brand communications, customer experience with company, brand awareness, brand meaning, and brand equity. The aggregate numbers of customer being respondent of the study are 150. Data analysis used in this research wasconsists of Structural Equation Method by LISRELL 8.7 as software. The result of this research conclude that variable of company’s presented brand had effect to brand awareness, company’s presented brand had effect to brand meaning, external brand communications had effect to brand awareness, external brand communications had effect to brand meaning, customer experience with company had effect to brand meaning, brand mening had effect to brand equity, and brand awareness had effect to brand equity.Keywords : Brand equity, Hotels, Brand Awareness, Customer satisfaction